Nilai dan Relevansi Sejarah Perang Bagi Pertahanan Negara - Bayu Hartono; Budi Sumaryono; Joni Widjayanto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The study of war history plays a strategic role in shaping national insight, discipline, and moral foundations that strengthen the national defense system. Understanding historical events of warfare not only provides knowledge about military tactics and strategies but also instills philosophical values that form the basis for nation-building and character development. This study aims to analyze the historical values contained in war history and examine their relevance to Indonesia’s defense system in the modern era. The research employs a qualitative descriptive approach using the library research method, focusing on the analysis of various historical literatures, philosophical theories of war, and national defense policy documents.The findings reveal that war history contains strategic values such as resilience, leadership, and tactical intelligence, as well as moral values such as patriotism, solidarity, responsibility, and the spirit of sacrifice. These values have contributed to the formation of the Total Defense System, which emphasizes the involvement of all components of the nation in maintaining sovereignty and national security. In the era of globalization, the values derived from war history remain highly relevant to strengthening national defense awareness, enhancing resilience against multidimensional threats, and building a defense character that is adaptive and oriented toward global peace